Palladium-Catalyzed Csp3–H Bond mono-Aroyloxylation of O-Alkyl Substituted 2,4,6-Trimethoxybenzaldoxime Ethers - Qiao, Wen-Li; Shao, Ling-Yan; Hu, Ya-Hua; Xing, Li-Hao; Deng, Ke-Zuan; Liu, Hong-Wei; Liao, Dao-Hua; Ji, Ya-Fei (Synlett, 2018)
A palladium-catalyzed Csp3–H bond mono-aroyloxylation of O-alkyl substituted oxime ethers has been developed by using 2,4,6-trimethoxybenzaldoxime as an exo-type directing group with exclusive site-selectivity. With the wide range of masked aliphatic alcohol substrates and aromatic acid coupling partners, the protocol allows rapid access to various 2-alkyl substituted glycol derivatives in synthetically useful to good yields. The employed directing group is readily removed, accordingly affording valuable functionalized aliphatic alcohols. When the solvent from hybrid DCE/HFIP to CH3CN, non-directed oxidative cross-coupling is observed between the electron-rich aromatic ring of substrates and aromatic acid partners.
Keywords: palladium-catalysis; Csp3–H bond functionalization; aroyloxylation; masked aliphatic alcohol; oxidative cross-coupling